Allium stoloniferum (Amaryllidaceae, Allioideae), a new species from Sichuan, China - Cheng, Rui-Yu; Zhang, Shi-Yao; Tang, Zi-Jun; Lv, Yang-Hao; Wu, Yong-Qi; Ye, Zheng; Liu, Shu-Ye; He, Ming-Hao; Zhang, Yu-Fei; He, Xin-Qiang; Meng, Shi-Yong; He, Xing-Jin; et al. (Phytotaxa, 2025)
Allium stoloniferum, a new species from Northwest Sichuan Province, China, is described and illustrated herein. Morphological and phylogenetic evidence suggests that this species belongs to the Allium sikkimense group of the subgenus Reticulatobulbosa. It is very similar to A. paepalanthoides and A. plurifoliatum, but can be distinguished by the purplish-red, basal, and broader leaf blades at the base of the petiole and scape, the well-developed underground rhizomes, the hollow scape, and the coloration of the tepals. Phylogenetic analysis based on nuclear ribosomal internal transcribed spacers (ITS) and four cpDNA regions (atpI–atpH, trnV–ndhC, rpoB–trnC, trnL–trnF), further reveal that A. stoloniferum shows a close relationship with other species in the A. sikkimense group, including A. kangdingense, A. beesianum, A. zhegushanense, A. sikkimense, A. yuanum, and A. cyaneum. Detailed differences in morphological characteristics and habitat are also provided.